Digital Literacy Strategy Encourages Electronic MSMEs to Go Online - Abdelina Abdelina; Lilis Saryani; Juwita Handayani (International Journal of Economics, Management and Accounting, 2024)
The Covid-19 pandemic has reduced people's purchasing power and made people's activities all online. Digital literacy needs to be carried out by MSME actors, especially Electronic MSMEs, where they still carry out offline buying and selling activities both in terms of promotion, marketing, and service communication. This study aims to determine the implementation of digital literacy for Electronic MSME actors to go online. Digital literacy is an effort to change and develop activities based on skills and knowledge by using technology. This study uses a qualitative descriptive approach using data analysis techniques Reduction, Display and Conclusion. This research was conducted at the Electronic MSMEs, Padangsidimpuan City, North Sumatera. The results showed that 88% of the understanding of Electronic MSME technology was based on the digital literacy capabilities they had, obtained through digital literacy activities carried out and received many benefits for the online sales system.